THE EFFECT OF BAAMBOOZLE APPLICATION TO ENHANCE ENGLISH VOCABULARY MASTERY (A QUASI EXPERIMENT AT8TH GRADE MTS NUR RAHMA BENGKULU CITY) - Siti Barotut; Ferri Susanto; Febriani, Hanura (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using the Baamboozle application on the English vocabulary mastery of eighth-grade students at Madrasah Tsanawiyah Nur Rahma, Bengkulu City. This research used a quantitative approach with a quasi-experimental design involving class VIII Zubair as the experimental class and class VIII Sa'ad as the control class. The research sample consisted of 43 students selected using total sampling technique. Data were collected through pre-tests and post-tests, then analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, and Independent Samples t-test. The results showed that the experimental class’s post-test scores were higher than those of the control class. The Independent Samples t-test produced a calculated t-value of 5.581 with a significance value of 0.001 (P<0.05), indicating a significant difference between the two groups after the treatment. These findings demonstrate that the use of the Baamboozle application is effective in improving students’ English vocabulary mastery. Based on the results, it can be concluded that the Baamboozle application has a significant effect on the English vocabulary mastery of eighth-grade students at Madrasah Tsanawiyah Nur Rahma, Bengkulu City. Therefore, the Baamboozle application can be used as a game-based learning medium to support English vocabulary learning.